The psychology of language : from data to theory - Harley, Trevor A. (Hove, East Sussex : Psychology Press, Taylor & Francis Group, 2014)
"Now in full colour, this fully revised edition of the best-selling textbook provides an up-to-date and comprehensive introduction to the psychology of language for undergraduates, postgraduates, and researchers. It contains everything the student needs to know about how we acquire, understand, produce, and store language. Whilst maintaining both the structure of the previous editions and the emphasis on cognitive processing, this fourth edition has been thoroughly updated to include:the latest research, including recent results from the fast-moving field of brain imaging and studiesupdated coverage of key ideas and modelsan expanded glossary more real-life examples and illustrations.The Psychology of Language, Fourth Edition is praised for describing complex ideas in a clear and approachable style, and assumes no prior knowledge other than a grounding in the basic concepts of cognitive psychology. It will be essential reading for advanced undergraduate and graduate students of cognition, psycholinguistics or the psychology of language. It will also be useful for those on speech and language therapy courses.The book is supported by a companion website featuring a range of helpful supplementary resources for both students and lecturers"--
"This fully revised edition of the popular textbook provides an up-to-date and comprehensive introduction to the psychology of language for undergraduates, postgraduates, and researchers. It contains everything the student needs to know about how we acquire, understand, produce, and store language. The Psychology of Language, 4th Edition, covers all the main topics in the psychology of language, such as language production, comprehension, syntax and parsing, reading development, and word recognition. In addition, this text covers language acquisition, how language is related to thought, bilingualism and second language acquisition. Following a strong developmental theme, it also describes how children acquire language while demonstrating how this is related to the brain and to other aspects of cognition. Whilst maintaining both the structure of the previous editions and the emphasis on cognitive processing, this fourth edition has been thoroughly updated with all the latest and cutting-edge research. In particular, the book takes into account recent research into cognitive neuroscience and the relationship between language and the brain. The Psychology of Language, 4th Edition describes complex ideas in a clear and approachable style, and assumes no prior knowledge other than a grounding in the basic concepts of cognitive psychology. It will be essential reading for advanced undergraduate and graduate students of cognition, psycholinguistics or the psychology of language. It will also be useful for those on speech and language therapy courses. The Psychology of Language, 4th Edition, is supported by a companion website featuring a range of helpful supplementary resources for both students and lecturers"--
Includes bibliographical references (pages 495-568) and index.
ENH
Trim education
Keywords: Psycholinguistics; PSYCHOLOGY / Cognitive Psychology; LANGUAGE ARTS & DISCIPLINES -- General; English language